Antecedents and Outcome of Sustainable Environmental Manufacturing Practices - Adebambo, Hameed Olusegun; Ashari, Hasbullah; Nordin, Norani (International Journal of Management and Sustainability, 2014)
An increased demand has been placed on the manufacturing industries to be more responsible to their environment with respect to their product and processes. This demand is due to various antecedent factors driving sustainable environmental practices in manufacturing firms. However, environmental value is not only the concern of firms. The impacts of this environmental initiative on the performance of these firms are as well important. The aim of this study is twofold: (i) to propose a comprehensive framework that encompasses the antecedents and the outcome of sustainable environmental manufacturing practices and (ii) as a validation process for the developed instrument of the ongoing research for the identified constructs of the study. Data were collected from thirty respondents using a seventy-seven item instrument. The data collected was analyzed using SPSS software. The results of the Cronbach’s Alpha test reveal a strong internal reliability of the construct and the overall instrument. The research is significant because it explores the implementation of sustainable environmental manufacturing practices in Malaysia and validates the instrument in which most of these constructs still need further exploration.